Comparing substance use treatment initiation and retention between telehealth delivered during COVID‐19 and in‐person treatment pre‐COVID‐19. Issue 3 (16th January 2023) - Sistad, Rebecca E.; Enggasser, Justin; Livingston, Nicholas A.; Brief, Deborah
Abstract: Background and Objectives: A large portion of veterans referred to substance use disorder (SUD) treatment do not attend their first appointment or leave treatment prematurely. Telehealth options may increase access to care and treatment attendance. This study compared treatment initiation and retention between in‐person treatment pre‐COVID‐19 and telehealth treatment during COVID‐19 in a VA hospital outpatient alcohol and drug treatment clinic. Methods: Electronic health record data were collected on 373 veterans out of 481 referrals. Mixed logistic and negative binomial regression models were used for estimating the effect of treatment modality on treatment initiation and retention, respectively. Results: The odds of initiating treatment were 2.6 times greater when referred to a telehealth appointment during COVID‐19 compared to an in‐person appointment pre‐COVID‐19. Months retained in treatment postinitiation was similar between treatment modalities. Each month in treatment corresponded to a subsequently lower rate of treatment session attendance and by the fourth month, the average number of sessions attended was significantly lower for those receiving in‐person treatment compared to those receiving telehealth treatment. Conclusions and Scientific Significance: The odds of initiating SUD treatment and rate of treatment attendance over time was greater for services delivered via telehealth during COVID‐19 compared to in‐person pre‐COVID‐19. Extending telehealth services as an option for individual and group SUD treatment may promote treatment initiation and potentially higher rate of attendance over time. This study provides additional evidence for the feasibility and utility of rapidly expanding telehealth for veterans seeking outpatient substance use treatment.